Ginger (Zingiber officinale) Extract Reduces the Frequency of Nausea and Vomiting and Stability of Blood Pressure in Pregnant Women - Mufida Annisa Rahmawati; Fitria Aaisyah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Nausea and vomiting are common conditions during pregnancy that may compromise maternal nutrition, quality of life, and pregnancy outcomes. Pharmacological options are often limited due to concerns over fetal safety. Ginger (Zingiber officinale) has been proposed as a safe complementary therapy with potential antiemetic and circulatory benefits. This study aimed to evaluate the effect of ginger extract supplementation on nausea–vomiting frequency and blood pressure stability among pregnant women. A quasi-experimental study with a pre-test–post-test control group design was conducted on 40 pregnant women in their second trimester, divided into an intervention group (n=20) and a control group (n=20). The intervention group received 500 mg of standardized ginger extract once daily for 30 consecutive days, while the control group received standard antenatal care. The Pregnancy-Unique Quantification of Emesis (PUQE) questionnaire was used to assess nausea–vomiting frequency, and blood pressure (systolic and diastolic) was measured before and after the intervention. Data were analyzed using paired t-tests and independent t-tests, with a significance level of p0.05. The intervention group experienced a significant reduction in mean PUQE scores from the moderate to the mild category (p0.001), while no significant change was observed in the control group. Post-intervention comparisons showed a statistically significant difference in nausea–vomiting frequency between the two groups (p0.001). Blood pressure analysis revealed that the intervention group maintained more stable systolic and diastolic values, with a modest but significant improvement compared to the control group (p0.05). Supplementation with 500 mg of ginger extract once daily for 30 days significantly reduced nausea and vomiting and contributed to blood pressure stability among pregnant women. Ginger may be considered a safe and effective complementary therapy in antenatal care.